2018
DOI: 10.1002/joc.5716
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of precipitation and air temperature over western Canada using a regional climate model

Abstract: The Mackenzie River basin (MRB), which covers a geographic region from central Alberta of Canada to the coast of Arctic Ocean, has an area of approximately 1.8 × 106 km2. In this study, the regional climate of MRB, in particular the precipitation and air temperature from the late spring to the fall (May–October), was simulated using a regional climate model Weather Research and Forecasting (WRF). In the open water season of May–October, Mackenzie River provides a critical corridor for Canada's Arctic transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…However, there is not much research in evaluating the performance of microphysics schemes for Malaysia that has been documented. The performance of these schemes has been assessed in other regions including the middle latitude region [53], western Canada [54], southeast India [55], and the Shasta Dam watershed, northern California [56]. This study analysis determines that the microphysics schemes SBU and MDM showed significant performance when combined with the other cumulus schemes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is not much research in evaluating the performance of microphysics schemes for Malaysia that has been documented. The performance of these schemes has been assessed in other regions including the middle latitude region [53], western Canada [54], southeast India [55], and the Shasta Dam watershed, northern California [56]. This study analysis determines that the microphysics schemes SBU and MDM showed significant performance when combined with the other cumulus schemes.…”
Section: Discussionmentioning
confidence: 99%
“…In simulating the relevant climatic variables, e.g., temperature and precipitation, it is highly dependent on various physical process like; cumulus convection, planetary boundary layer (PBL), land surface, and microphysical processes [23][24][25] . Numerous studies have been undertaken with the WRF model to select the most suitable configuration for regional climate simulations [26][27][28] . WRF model capability to simulate very significant severe temperature events during HW days towards coastal regions of India.…”
Section: Description Of Weather Research and Forecasting (Wrf) Modelmentioning
confidence: 99%
“…Through results estimated from conducting various test runs, the schemes of WRF chosen are the Kain-Fritsch cumulus scheme (Kain 2004), WRF Double-Moment 6-class Microphysics scheme (Lim and Hong 2010), CAM Longwave (LW) and Shortwave (SW) radiation scheme (Collins et al 2004), the Yonsei University PBL (planetary boundary layer) scheme (Hong et al 2006), and the Noah LSM (Chen et al 1996(Chen et al , 1997. These configurations simulated representative climate for the Mackenzie River Basin (Kuo and Gan 2018). Given developing IDF curves require sub-hourly precipitation data, the outputs of WRF at 15-min time intervals for the innermost domain (D3) were used to estimate the grid-based IDF curves of Edmonton.…”
Section: Rcm Configurations and Post-processingmentioning
confidence: 99%